(untitled) (Research, Society and Development, 2024)
Food hypersensitivity in dogs is an immune-mediated condition that causes adverse reactions to certain allergens present in the diet, and is one of the main dermatopathies seen in pets. The aim of this study was to evaluate the clinical, diagnostic and therapeutic aspects of food hypersensitivity in dogs. The methodology involved a narrative review of the literature, based on scientific articles available in databases such as Google Scholar, PubMed and Scielo, focusing on terms such as food allergies and allergic dermatopathies. The results indicate that the condition is mainly manifested by non-seasonal pruritus, erythema, otitis and, in some cases, gastrointestinal symptoms. Diagnosis is made through exclusion diets, which are followed by provocation diets to identify specific allergens. Treatment is based on excluding the allergens detected, using commercial or homemade hypoallergenic diets, which requires the strict cooperation of the owner and veterinary supervision. Although it is an incurable condition, the prognosis is generally positive if allergens are avoided. The study concludes that, despite the difficulties in diagnosis and long-term management, proper diet control and the elimination of allergens provide a significant improvement in the quality of life of dogs.